SWOT Strategy in Strengthening the Role of Village Community Empowerment Institutions: An Islamic Law Perspective - Abdullah, Fadli Daud; Sulistiyo, Budi; Wiwaha, Syahid Mujahid (Jurnal Al Maesarah, 2024)
This research addresses important issues identified during capacity-building study meetings, including community confusion regarding the function of community empowerment institutions, low levels of participation, and fragmented stakeholder perceptions, all of which impact the effectiveness of village development. This research uses qualitative methods; data collection involves interviews and literature reviews. SWOT analysis assesses the strengths, weaknesses, opportunities, and challenges of community empowerment institutions. Analysis shows that community empowerment institutions have difficulty facilitating community input and holding development planning meetings effectively, thereby hampering participatory governance. Despite these challenges, the Institute has demonstrated strength in mediating community-government dialogue and motivating communal efforts, although improvements in program evaluation and structural cohesion are needed. The study found that the institute is in line with Islamic principles such as ukhuwwah (brotherhood) and ta'awun (cooperation) by empowering communities through inclusive development planning and mutual cooperation. This research concludes that the implementation of Law Number 6 of 2014 by the Community Empowerment Institute has had a positive impact despite the challenges. This research recommends increasing community awareness, strengthening institutional capacity, and fostering greater synergy between institutions and village governments to achieve sustainable and inclusive development.